The impact of extent and variety in active learning methods across online and face-to-face education on students’ course evaluations - Beimel, Dizza; Tsoury, Arava; Barnett-Itzhaki, Zohar (Frontiers in Education, 2024)
In recent years, numerous studies have compared traditional face-to-face (F2F) learning on campus with online learning, seeking to establish how the learning environment (online vs. F2F) affects outcomes such as student satisfaction and achievement. In a separate line of research, scholars have examined various facets of active learning-an approach that makes use of interactive learning methods-separately in online and F2F environments. However, few studies have compared the effects of active learning in classes taught online vs. F2F. The present study addresses this gap. It follows an earlier study in which we examined the effects of active learning in an online environment, particularly how the extent and variety of interactive teaching methods used affect students' course evaluations (overall evaluations and perceived clarity of the teaching). The present study repeats the setup of that previous study in a F2F environment, allowing us both to gain new insights into the effects of active learning in this context and also to directly compare the examined outcomes in F2F vs. online learning. The results reveal consistent trends in both studies: more extensive and more varied use of interactive learning methods improves overall student evaluations and perceptions of the clarity of teaching in the course. Crucially, minimal use of interactive teaching methods results in notably lower student evaluations and perceptions of teaching clarity in face-to-face (F2F) settings compared to online classes. This The findings highlights the essential need for instructors to adopt diverse interactive methods in F2F environments to improve educational outcomes and reinforce the effectiveness of active learning.